TESTING THE EFFECT OF SUBJECTIVE NORM MODERATION ON LUXURY PRODUCTS - Ariamurti, Febby; Tunjungsari, Hetty Karunia (International Journal of Application on Economics and Business, 2023)
The aim of this research is to examine the moderating role of subjective norm values. This study uses primary data with the target population being consumers who wish to purchase luxury products in the next year in Jakarta. The data collection process was carried out by distributing questionnaires online through the media google form. The sample collection method uses non-probability sampling with purposive sampling with 200 respondents. The data analysis technique used is Structural Equation Modeling (SEM) with SmartPLS software version 3.2.9. The results of this study found that attitudes, subjective norms and perceptions of behavioral control influence purchase intention and attitudes toward purchase intentions with moderation of subjective norms but perceptions of behavioral control on buying interest with moderation of subjective norms have no effect.